Archive Management at Balai Arsip and Tsunami Aceh - Andayani, Sri (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2018)
The archive records the truth of a fact or activity of an institution, whether it is an activity that is being done or has happened at a previous time. Therefore, archives must be well organized in order to remain systematic and sustainable. This paper describes how static archive management at Balai Arsip and Tsunami Aceh. The management of the archives at Balai Arsip dan Tsunami Aceh refers to the Regulations of the Archive of the Republic of Indonesia (ANRI), which is responsible for acquisition, processing, preserving and archiving services to the public. In practice, archive management has constraints that are limited storage space and human resources.